The LOB STROKE MODEL IN LEARNING BADMINTON GAME FOR ELEMENTARY SCHOOL STUDENTS CLASS V - Indira, Fauzalina; Samsudin (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2023)
The purpose of this study was to obtain information about the process of implementing badminton game learning, practice the learning process with the badminton lob model for elementary school students in grade V, and obtain empirical data about the effectiveness, efficiency, and student interest in the learning process of badminton lob stroke for elementary school students. grade 5. This research was conducted at SDN Makasar 05 Pagi, East Jakarta, with 31 students as the research object. This study uses the ADDIE learning development model, which starts at the Analysis, Design, Development, Implementation, and Evaluation stages. From the results obtained, this badminton lob learning model turned out to be very effective when applied to learning. This can be seen from the increase in the results of the skills assessment of students at SDN Makasar 05 Pagi Class VA.